Workshop Marketing Digital Siswa SMK Negeri Rawas Ulu - Alfiarini; Deni Apriadi; Robi Yanto (Jurnal Pengabdian kepada Masyarakat Radisi, 2022)
Technological developments and the emergence of the industrial revolution 4.0 are one of the big challenges that must be faced. Many impacts arise and will have an impact on the absorption of human resources. One of the solutions that the government has taken is to include an entrepreneurship curriculum in an effort to strengthen economic programs. Marketing is one method that can be used to support the entrepreneurship curriculum. The entrepreneurship curriculum for high school vocational programs is limited to how to produce a product, but does not teach marketing. Limited knowledge related to marketing makes it difficult for businesses to compete. Digital marketing is a technique that can be used to promote products via the internet. The method of implementing this activity consists of 3 (three) stages, namely the preparation stage, the implementation stage, and the evaluation stage. Based on the initial stages, it was found that there was still a lack of insight into students at the Rawas Ulu State Vocational School regarding digital marketing and optimizing the use of the internet for marketing. After the workshop was carried out, it was found that students' knowledge of digital marketing had increased to 75.43% from the pre-test results data which was originally only 45.75% increased to 29.68%.